Metacognitive Experiences in Consumer Judgment and Decision Making - Schwarz, Norbert (Journal of Consumer Psychology, 2004)
Human reasoning is accompanied by metacognitive experiences, most notably the ease or difficulty of recall and thought generation and the fluency with which new information can be processed. These experiences are informative in their own right. They can serve as a basis of judgment in addition to, or at the expense of, declarative information and can qualify the conclusions drawn from recalled content. What exactly people conclude from a given metacognitive experience depends on the naive theory of mental processes they bring to bear, rendering the outcomes highly variable. The obtained judgments cannot be predicted on the basis of accessible declarative information alone; we cannot understand human judgment without taking into account the interplay of declarative and experiential information.